Numerical simulation of cavitation for a horizontal axis marine current turbine. Issue 4 (15th January 2015) - Guo, Q; Zhou, L J; Wang, Z W
Abstract: Marine current turbines, compared with the analogous wind turbines, have the potential to suffer cavitation. This paper focuses on the effect of cavitation on a marine current turbine and implements the two-phase flow simulations based on the Rayleigh-Plesset cavitation model. It can be found that under the influence of cavitation, the power and thrust coefficients of turbine decrease and especially near the blade tips. Due to the non-uniform hydrostatic pressure along the depth of water, the present work takes this effect into account and finds a larger cavitation area appears on the blade tips at a shallow submergence. Meanwhile the power and thrust performance of one blade change during its rotating period. In order to analyze the cavitation performance of turbine locates at a certain water depth, the variations of inflow velocity and rotor rotating speed are implemented. It indicates that, with the inflow velocity increasing, the CP and CT of turbine with higher rotation speed will significantly reduce due to the occurrence of cavitation, and the influence on the turbine with lower speed is small. These predicting results can provide implications for the safe and stable operation of marine current turbines.